Bio-ink development for food printing - Quek, Wei Xiang (Nanyang Technological University, 2024)
3D printing has gained popularity in the food industry because of its benefits, such as the capability to improve structure, texture, and nutritional qualities of food. However, successful creation of high-quality 3D printed foods is dependent on the availability of edible bio-inks that possess the required properties. This study centers on developing composite food hydrogels for 3D printing applications, specifically for meat printing, by analyzing two different compositions of bio-ink: Bovine Gelatin-Gelzan-Pectin and Fish Gelatin-Gelzan-Genipin. A detailed assessment was conducted to characterize the ink formulations by examining their rheological properties, thermal stability, and mechanical properties to determine their suitability for creating precise food shapes. The findings suggest that optimized bio-ink formulations can significantly improve the versatility and functionality of food printing technologies, offering promising prospects for personalized nutrition and intricate food design.